A Primal Perspective on the Philosophy of Religion - Sharma, Arvind. author. aut Link
XII, 246 p.
Keywords: The philosophy of religion has been a largely European intellectual enterprise in two ways. It arose in Europe as a discipline and its subject matter has been profoundly influenced by Christianity as practised in Europe. The process of its deprovincialization in this respect started when it began to take religions other than Christianity within its purview - such as Hinduism, Buddhism, and Islam. Although now the religions of both East and West have found a place in it, a religious tradition which is present in both the East and the West, namely, the primal religious tradition, still remains unrepresented in its discussions, perhaps under the mistaken assumption that this religious tradition has little to offer by way of philosophical reflection. This book challenges this widespread assumption and demonstrates how primal religions have something significant to offer on virtually every theme discussed in the philosophy of religion. Through this book the primal religous tradition stakes its claim for a place at the table. "Despite the absence of written texts, primal religions have an implicit philosophy. They can offer a fresh perspective on controversial philosophical issues. This study shows how materials of primal religious experience can be incorporated in the categories of modern philosophy of religion. Fourteen chapters offer examples varying from concepts of God and revelation to conflicating truth claims and the problem of human destiny. The book contends that the primal perspective can widen and deepen the horizons of philosophy of religion and enhance the philosophical appreciation of religion as a universal phenomenon." Jacobus Waardenburg, University of Lausanne, Switzerland "Arvind Sharma makes a perfect case for a cross-cultural philosophy of religion in which all world religions, especially primal religions, could effectively participate in the dialogue and conversation about the relevant issues in the questfor the transcendent and the sacred. The work ultimately may be a prolegomena to the study of philosophy of religion of many primal religious traditions, because it provokes debate and responses from scholars of these traditions. This book will certainly begin a broader conversation in the cross-cultural philosophy of religion." Jacob Olupona, The University of California, Davis, U.S.A.